2019
DOI: 10.3389/fpls.2019.00900
|View full text |Cite
|
Sign up to set email alerts
|

A Role for PICKLE in the Regulation of Cold and Salt Stress Tolerance in Arabidopsis

Abstract: Arabidopsis PICKLE (PKL) is a putative CHD3-type chromatin remodeling factor with important roles in regulating plant growth and development as well as RNA-directed DNA methylation (RdDM). The role of PKL protein in plant abiotic stress response is still poorly understood. Here, we report that PKL is important for cold stress response in Arabidopsis. Loss-of-function mutations in the PKL gene lead to a chlorotic phenotype in seedlings under cold stress, which is caused by the alterations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(50 citation statements)
references
References 51 publications
3
43
0
Order By: Relevance
“…A recent study indicated that the chromatin remodeler PICKLE (PKL) participates in the CBF‐dependent cold stress response in Arabidopsis . The Arabidopsis pkl mutants are hypersensitive to chilling and cold stress treatments (Yang et al 2019). The expression of the transcription factor gene CBF3 and of downstream COR family genes such as COR15B and RESPONSIVE TO DEHYDRATION 29A ( RD29A) was downregulated in the pkl mutants after 3 h of cold treatment compared to that in wild‐type plants.…”
Section: Epigenetic Regulation During the Extreme‐temperature Stress mentioning
confidence: 99%
“…A recent study indicated that the chromatin remodeler PICKLE (PKL) participates in the CBF‐dependent cold stress response in Arabidopsis . The Arabidopsis pkl mutants are hypersensitive to chilling and cold stress treatments (Yang et al 2019). The expression of the transcription factor gene CBF3 and of downstream COR family genes such as COR15B and RESPONSIVE TO DEHYDRATION 29A ( RD29A) was downregulated in the pkl mutants after 3 h of cold treatment compared to that in wild‐type plants.…”
Section: Epigenetic Regulation During the Extreme‐temperature Stress mentioning
confidence: 99%
“…Besides DNA methylation and histone modifications, chromatin structure and gene expression may also be affected by chromatin remodeling, a process that disrupts histone-DNA interactions resulting in the altered accessibility of specific DNA regions to transcription machinery [79,80]. Chromatin remodeling factor (CHR), including the SWI/SNF ATPases, the imitation switch (ISWI) ATPases, and the chromodomain and helicase-like domain (CHD) ATPases subfamilies, could mediate either the ATP-dependent chromatin remodeling or the posttranslational histone modifications [57,58,[73][74][75][76][77][78][79][80][81][82][83][84]. The ATP-dependent chromatin remodeling complexes could alter nucleosome composition, and positioning and thus regulate DNA accessibility and gene expression.…”
Section: Chromatin Remodelingmentioning
confidence: 99%
“…In Arabidopsis, mutations in some genes involved in the regulation of COR gene expression, have been shown to exhibit ABA hypersensitive phenotypes (Perruc et al, 2007;Belin and Lopez-Molina, 2008;Kang et al, 2018). An example of such a regulatory gene is PKL, a putative CHD3-type chromatin remodeling factor with important roles in plant growth and development and responses to abiotic stress (Yang et al, 2017(Yang et al, , 2019. This indicates that, at least some COR proteins have regulatory roles in ABA-dependent responses.…”
Section: Discussionmentioning
confidence: 99%